Stability Analysis of Hepatitis B Virus Model with Incomplete Immunization of HepB Vaccine - Yan Cheng; Qiuhui Pan; Mingfeng He (Abstract and Applied Analysis)
In this paper a HBV infection model with impulsive vaccination is considered. By using fixed point theorem and stroboscopic map we prove the existence of disease-free T-periodic solution. Also by comparative theorem of impulsive differential equation we get the global asymptotic stability of the disease-free periodic solution and permanence of the disease. Numerical simulations show the influence of parameters on the dynamics of HBV, which provided references for seeking optimal measures to control the transmission of HBV.